Serum tryptase concentration and progression to end‐stage renal disease. (15th April 2016) - Jesky, Mark D.; Stringer, Stephanie J.; Fenton, Anthony; Ng, Khai Ping; Yadav, Punit; Ndumbo, Miguel; McCann, Katerina; Plant, Tim; Dasgupta, Indranil; Harding, Stephen J.; Drayson, Mark T.; Redegeld, Frank; et al.
Abstract: Background: Mast cell activation can lead to nonclassical activation of the Renin–Angiotensin–Aldosterone System. However, the relevance of this to human chronic kidney disease is unknown. We assessed the association between serum tryptase, a product of mast cell activation, and progression to end‐stage renal disease or mortality in patients with advanced chronic kidney disease. We stratified patients by use of angiotensin‐converting enzyme inhibitors/angiotensin receptor II blockers (ACEi/ARB). Materials and methods: This was a prospective cohort study of 446 participants recruited into the Renal Impairment in Secondary Care study. Serum tryptase was measured at recruitment by sandwich immunoassay. Cox regression analysis was undertaken to determine variables associated with progression to end‐stage renal disease or death. Results: Serum tryptase concentration was independently associated with progression to end‐stage renal disease but not with death. In patients treated with ACEi or ARB, there was a strong independent association between higher tryptase concentrations and progression to end‐stage renal disease; when compared to the lowest tertile, tryptase concentrations in the middle and highest tertiles had hazard ratios [HR] of 5·78 (95% confidence interval [CI] 1·19–28·03, P = 0·029) and 6·19 (95% CI 1·49–25·69, P = 0·012), respectively. The other independent risk factors for progression to end‐stage renal disease were lower age, male gender, lower estimated glomerular filtration rate and higher urinary albumin creatinine ratio. Conclusion: Elevated serum tryptase concentration is an independent prognostic factor for progression to end‐stage renal disease in patients with chronic kidney disease who are receiving treatment with an ACEi or ARB.